A Varied History of an Influential Author/Publisher Society – The VG WORT (KULT_online, 2009)
The Verwertungsgesellschaft Wort’s (VG WORT) fiftieth anniversary in 2008 occasioned this jubilee edition edited by Thomas Keiderling, whose task it is to introduce the complex and initially confusing remit of the Verwertungsgesellschaft (collecting society) in an accessible way: a non-profit collecting society that works on behalf of authors and publishers in matters of copyright. The society’s history and background are presented in a well-grounded and problem-oriented way. The book details the society’s founding, profiles prominent members and explicitly discusses law suits and test cases. Completing the volume are seven essays from some of the society’s leading innovators. Keiderling’s is a highly readable account of the VG WORT, suitable for scholars and laymen alike.